Theory of mind: mechanisms, methods, and new directions - Byom, Lindsey J.; Mutlu, Bilge (Frontiers in Human Neuroscience, 2013)
Theory of Mind (ToM) has received significant research attention. Traditional ToM research has provided important understanding of how humans reason about mental states by utilizing shared world knowledge, social cues, and the interpretation of actions, however many current behavioral paradigms are limited to static, “third-person” protocols. Emerging experimental approaches such as cognitive simulation and simulated social interaction offer opportunities to investigate ToM in interactive, “first-person” and “second-person” scenarios while affording greater experimental control. The advantages and limitations of traditional and emerging ToM methodologies are discussed with the intent of advancing the understanding of ToM in socially mediated situations.